Influence of common palynological extraction treatments on ultraviolet absorbing compounds (UACs) in sub-fossil pollen and spores observed in FTIR spectra - Wang, Tianyuan; Bell, Benjamin A.; Fletcher, William J.; Ryan, Peter A.; Wogelius, Roy A. (Frontiers in Ecology and Evolution, 2023)
Biological life, atmospheric circulation and the Earth’s climate may be influenced by UV-B radiation. In plants, Ultraviolet Absorbing Compounds (UACs) are an indicator of UV-B exposure, and the abundance of UACs in pollen and spores of embryophytes is measurable using Fourier Transform Infrared (FTIR) micro-Spectroscopy. However, understanding the influence of common chemical pre-treatments on sub-fossil pollen and spores with a view to UV-B reconstruction still requires investigation. Here, peat samples collected from a Late Holocene raised bog were treated with different chemicals (HCl, KOH, and acetolysis) for varying treatment times (up to 210 minutes). Pollen or spores of three common taxa (Alnus, Calluna and Sphagnum) were isolated and FTIR spectra obtained on individual grains. The spectra were compared to modern pollen samples collected nearby. Spectra of modern and sub-fossil samples show several visible differences related to lipid and protoplast contents. The results of chemical treatments on sub-fossil pollen and spores reveal that HCl produced limited changes, while KOH and acetolysis altered several peaks, including the UAC-related aromatic peak at 1516 cm-1. Specifically, we observe that all treatments modify the FTIR spectra to some degree, from weakest (HCl) to strongest (acetolysis). With respect to reduction of UAC peak area and treatment time, we observe in some cases a significant log-decay relationship, notably for KOH treatment on Calluna pollen and acetolysis on Sphagnum spores. Compared to untreated control samples, UAC peak area in Alnus, Calluna and Sphagnum reduced by 68%, 69% and 60% respectively, after only 3 minutes of acetolysis treatment. After 60 minutes of treatment UAC peaks were reduced by 77%, 84% and 89%. Therefore, due to the potential for taxon-specific effects and significant reductions in UAC peak area even within short treatment times, our recommendation for future applications in palaeoecological studies on palynomorph chemistry is to avoid chemical digestions in the pollen extraction process in favour of separation methods including micro-sieving and density separation.